Open-bite malocclusion : treatment and stability - Janson, Guilherme dos Reis Pereira; Valarelli, Fabricio (Wiley Blackwell, 2014)
Open-Bite Malocclusion: Treatment and Stability presents the etiology, treatment, and its stability of anterior open bite malocclusion in the early, mixed, and permanent dentitions. Special emphasis is devoted to orthodontic treatment and its stability in the permanent dentition because this is the time when treatment of open bite presents greater relapse. Appropriate for clinicians, orthodontic residents, and dental students, Open-Bite Malocclusion covers the most simple treatment approaches to the most complex, from orthodontic devices to tooth extraction to surgery.